Myogenic Differentiation Potential of Mesenchymal Stem Cells Derived from Fetal Bovine Bone Marrow - Okamura, Lucas Hidenori [UNESP]; Cordero, Paloma; Palomino, Jaime; Hugo Parraguez, Victor; Gabriel Torres, Cristian; Peralta, Oscar Alejandro (Taylor & Francis Inc, 2018)
The myogenic potential of bovine fetal MSC (bfMSC) derived from bone marrow (BM) remains unknown; despite its potential application for the study of myogenesis and its implications for livestock production. In the present study, three protocols for in vitro myogenic differentiation of bfMSC based on the use of DNA methyltransferase inhibitor 5-Aza-2-deoxycytidine (5-Aza), myoblast-secreted factor Galectin-1 (Gal-1), and myoblast culture medium SkGM-2 BulletKit were used. Plastic-adherent bfMSC were isolated from fetal BM collected from abattoir-derived fetuses. Post-thaw viability analyses detected 85.6% bfMSC negative for propidium iodine (PI). Levels of muscle regulatory factors (MRF) MYF5, MYF6, MYOD, and DES mRNA were higher (P<0.05) in bfMSC cultured under 100 mu M of 5-Aza compared to 1 and 10 mu M. Treatment of bfMSC with 10 mu M of 5-Aza resulted in down-regulation of MYOD mRNA (Days 7 to 21) and up-regulation of MYF6 (Day 7), MYF5, and DES mRNA (Day 21). Gal-1 and SkGM-2 BulletKit induced sequential down-regulation of early MRF (MYF5) and up-regulation of intermediate (MYOD) and late MRF (DES) mRNA. Moreover, DES and MYF5 were immunodetected in differentiated bfMSC. In conclusion, protocols evaluated in bfMSC induced progress into myogenic differentiation until certain extent evidenced by changes in MRF gene expression.
Keywords: Bone marrow; cattle; mesenchymal stem cells; myogenesis